Anemia and Erythropoietin Use Among Hemodialysis Chronic Kidney Disease Patients at Rumah Sakit Umum Siloam - Tjiang, Margaret Merlyn; Caroline, Elliscia; Siregar, Jeremia Immanuel (Medicinus, 2024)
Background: Chronic kidney disease (CKD) affects an estimated 8-16% of the population and is increasing in prevalence. Anemia, a common and significant complication of CKD, is primarily caused by reduced erythropoietin production, which is essential for red blood cell production. Erythropoietin, a kidney-produced hormone, stimulates bone marrow to produce red blood cells. This study examines trends in the use of erythropoiesis-stimulating agents (ESAs) and the management of anemia in dialysis CKD patients before and after the implementation of ESA reimbursemen.Methods: This cohort study was conducted at Rumah Sakit Umum Siloam, Tangerang, Indonesia, from February to July 2017. Patients who received blood transfusions or iron supplements during the study were excluded. Data collected included age, gender, dry weight, history of diabetes mellitus, hypertension, hemodialysis adequacy, and nutritional status. Statistical analysis with a 95% confidence interval (CI) was used to assess the association between hemoglobin levels (Hb) and erythropoietin use.Results: Sixty patients completed the study. The proportion of anemic patients (Hb <10 g/dL) increased from 22 (36.7%) to 28 (46.7%) after erythropoietin administration. A mean dose of 6000 IU/week (CI: 4679 to 7321 IU/week) was effective in achieving target hemoglobin levels, while a dose of 4131 IU/week (CI: 3479 to 4782 IU/week) was sufficient to maintain them. Additionally, a dosage of 103.31 IU/kg/week increased hemoglobin by 1 g/dL in anemic patients.Conclusions: Erythropoietin use should be optimized given the increasing prevalence of anemia. A dosage of 103.31 IU/kg/week is recommended to achieve target hemoglobin levels, while 4131 IU/week is suggested for maintaining hemoglobin within the target range.